Control biológico de Meloidogyne spp en áreas cultivadas con caña de azúcar (Saccharum officinarum) - Vaca Anchundia, Jhon Alberto (2021)
It is important to address the problem of nematode parasitism in sugarcane, especially in countries where this crop is of great economic importance. It has been proven that the increase in yield and production in sugarcane is notorious for the aggressive reduction of the density of the nematode community shortly after planting and harvesting. It is common knowledge that the sugarcane crop is not free from attack by various species and numbers of nematodes. Most of the phytoparasitic nematodes are directly responsible for causing damage to the root system in sugarcane crops, resulting in the plants' inability to absorb water and nutrients from the soil. The most common nematode found in sugarcane is Meloidogyne spp, which forms galls on the roots. Biological control is recommended, since chemical control is detrimental to the surrounding environment and, above all, affects the health of living beings that consume sugarcane. One of the main biological controllers are the nematodes of Pasteuria penetrans since it has greater efficacy in the control of Meloidogyne. Pasteuria penetrans is currently performed by in vitro culture media on the roots of a crop infested by Meloidogyne spp. Its eminent development is observed as a commercial bioproduct of great effectiveness on the most economically important phytoparasitic nematodes worldwide. Another of the phytonemates effective in the control of Meloidogyne spp. is the nematode Bacillus subtilis, an effective antagonist to combat gill-forming nematodes and can be used in the management of economic crops, in order to reduce the harmful effects of the parasite with the help of endotoxins produced by B. subtilis in the soil that interfere in the reproductive cycle of the nematodes, mainly in the oviposition and hatching of the juveniles.